An Investigation of Joining Polyamide (PA) to Stainless Steel AISI 316L by Hot Press Process - Osamah Sabah Barrak; Osamah Fattah Taresh; Mahmood Mohammed Hamzah; Rusul Ahmed Shakir (Journal of Techniques)
A hot press process was used as a technique to pound a polyamide type of polymer of a thickness (2mm) to stainless steel AISI 316L of the thickness (1mm). A hybrid joint of dissimilar material was accomplished by a hot press bonding process.  During the joining process, three different parameters of process were used:  processing temperature of 175, 170 and 165°C, processing pressure of 3, 6 and 9 bar and time of 1.5, 3 and 4.5 min. The surface of stainless steel was prepared and treated by a mechanical treatment (surface grinding) to improve the wettability to increase the shear strength. A shear tensile, scanning electron microscope (SEM) and energy dispersive spectrometry (EDS) tests were used to investigate and examine the joint (bounding) specimens. The Minitab program was used to analyze the effect of the parameters of the joining process on the joint properties. The maximum and minimum values of shear force are exhibited at a processing temperature of 165°C, applied pressure of 6 bars and processing time of 1.5 minutes; the minimum shear force was found to be 675 N, while the maximum shear force was 2182 N at a processing temperature of 175°C, applied pressure of 6 bars and processing time of 3 minutes.  The tested joints failed by an interfacial shear and necking in the polymer side with a ductile fracture. The joining process occurred through a mechanical interlocking between the molten polymer and the treated surface of the steel specimen. The average thickness of the joining line for the tested specimens was 8µm.